Promoting Lithuania’s Competitiveness through Entrepreneurship: the Results of Expert Assessment - Petuškienė, Edita; Glinskienė, Rasa (Socialiniai tyrimai, 2016)
In economy, the role of entrepreneurship has been insufficiently and comprehensively analyzed, especially in the works of Lithuanian authors. To be precise, there is a number of studies that examine the entrepreneurship phenomenon through innovations, as a result of entrepreneurs’ actions, entrepreneurship effects on unemployment reduction, etc. but works where the impact of entrepreneurship on national economy and its ability to promote national competitiveness in the global arena are lacking. Despite the fact that the scientific entrepreneurship theory proposes a rather contradictory attitude to the amount of its influence on some general macroeconomic indexes, this exploratory research, based on expert assessment, gives a valid reason to continue research on entrepreneurship as a tool for the promotion of Lithuania’s competitiveness.